Smart Approaches of Nanosponge-loaded Gels of Ketoconazole for Topical Delivery - Ahuja, Ashima (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The present study was done to formulate ketoconazole (KET) nanosponges (NSs) using ethyl cellulose polymer using the solvent evaporation method. Materials and Methods: The prepared NSs were subjected to a drug-polymer incompatibility study using Fourier transform infrared analysis. In addition, formulations F1-F6 were evaluated for various parameters such as percentage yield, % entrapment efficiency (EE), % drug content, in vitro release study, and particle size determination using scanning electron microscopy analysis. Results and Discussion: KET-loaded EC nanosponges F6 optimized formulation showed superior % drug content, % yield, and EE, showing extended drug release of drug (84.48%) at the end of 240 minutes. Optimized formulation was loaded into HPMC gel and evaluated for pH, viscosity, extrudability, and % drug content. KET-NSs-loaded HPMC gel (GK5) showed optimal pH (4.24), good spreadibility (23.76 g.cm/sec), extrudability (96.14%), and viscosity (3567 cp). In vitro antifungal study revealed that KET-loaded NSs showed potent antifungal activity against C. albicans. GK5 formulation loaded with HPMC effectively targets fungal infection and is effective for topical delivery. Conclusion: The findings revealed that the nanosponges-loaded gel was effective for antifungal delivery.